UMP vehicle entry system using QR code - Abi Shaiful, Yusuff (2018)
In daily life of the University Malaysia Pahang area, safety and well-being is the priority of both students and staff among University society. Lately there are vehicle theft problems like motorcycle theft and car theft. To ensure the safety of vehicles in the University is controlled, the University Safety Division requires a system to record student information and vehicle information they use in University Malaysia Pahang. By referring to the problem, the University Vehicle Entry system is developed to filter and store data on all vehicles inside this area. The objective of this project is to develop an application to scan vehicles are located in the University via a QR code scan. When entering to the University users should only scan the QR code displayed on the screen at the guard post. The application is expected to assist the University's Security Division in detecting if thefts were happened. Repeated methodology was selected for the implementation of this project, there are six departments in this methodology, planning, design, requirements, design, implementation, testing, and dissemination. Upon completion of all appointments, a usability test will be conducted to get the app user's reactions so that the system can be restored. This process is carried out to ensure the objective of this system is achieved.